The relict plant Tetraena mongolica plantations increase the nutrition and microbial diversity in desert soil - Yanan Quan; Yanan Quan; Yanan Quan; Xiuwen Gan; Xiuwen Gan; Xiuwen Gan; Shiyun Lu; Shiyun Lu; Shiyun Lu; Xiaodong Shi; Xiaodong Shi; Xiaodong Shi; et al. (Frontiers in Plant Science)
IntroductionTetraena mongolica was established in the West Ordos Region of northwest China approximately 140 million years ago. It plays an irreplaceable role in maintaining local ecosystem stability. MethodsThis study aimed to evaluate the effects of planting T. mongolica on soil nutrition and microbial communities by comparing the root zone soil (Rz_soil) and bare soil (B_soil) across three different plant communitie. ResultsThe results showed that T. mongolica decreased soil pH and Na+ while increasing available potassium, soil organic matter, organic carbon, total nitrogen, and potassium. T. mongolica significantly improved the diversity indices (Sobs and Ace), as well as the richness index (Chao), of bacterial and fungal communities across three plant communities. Meanwhile, the relative abundances of Rubrobacter and norank_c_Actinobacteria in the bacterial communities declined significantly in the Rz_soil compared with the B_soil across all three plant communities. In contrast, the relative abundances of Fusarium and Penicillium were higher, whereas those of Monosporascus and Darksidea were lower in Rz_soil than in B_soil in the two plant communities. T. mongolica decreased the soil bacterial co-occurrence networks while increasing the soil fungal co-occurrence networks. DiscussionThese results provide a new perspective to understand the role of T. Mongolica in the desert ecosystems.